Shared molecular profiles of post-laser vision correction ectasia and keratoconus with key differences in CADPS, CPT1B, CIITA, and TBC1D4 - Jaskiewicz-Rajewicz, Katarzyna; Wysocka, Alicja; Maleszka-Kurpiel, Magdalena; Matuszewska-Mach, Eliza; Wozniak, Jakub; Ploski, Rafal; Matysiak, Jan; Rydzanicz, Malgorzata; Gajecka, Marzena (Frontiers in Molecular Biosciences, 2025)
IntroductionPost-laser vision correction (post-LVC) ectasia is a serious complication that is observed in 0.033%–0.66% of corneal refractive surgeries. Similar to keratoconus (KTCN), post-LVC ectasia is classified under the category of “ectatic diseases.” We hypothesize that although the mechanistic aspects of post-LVC ectasia and KTCN are distinct, there are notable similarities in the epithelial responses, including shared molecular features.MethodsA total of 11 post-LVC ectasia, 8 mild myopia (controls), and 28 KTCN patients were included in a retrospective multiomics case–control study. The corneal epithelium (CE) samples obtained from the subjects were separated into different topographic regions (TRs: central, middle, and peripheral), and a total of 159 experimental samples were subjected to transcriptome (RNA-Seq) and proteome (MALDI-TOF/TOF MS/MS) profiling. The results were then verified/validated using reverse transcription quantitative polymerase chain reaction, immunofluorescence staining, and confocal microscopy in the extended sample set (n = 21).ResultsThe residual stromal bed, stromal ablation depth, and percent tissue altered indices were found to best predict the risk of post-LVC ectasia. From comparisons of post-LVC ectasia and KTCN, interferon-alpha and interferon-gamma hallmarks were found to be downregulated in the central and middle TRs of the CE of patients with post-LVC ectasia. Downregulation of CADPS gene expression was confirmed in all three TRs in the extended CE sample set. Cytoplasmic localizations of the CIITA and TBC1D4 proteins, which are the candidate post-LVC ectasia-specific biomarkers, were demonstrated in the CE samples. DiscussionThe assessment of CADPS, CPT1B, CIITA, and TBC1D4 gene expressions could enhance the risk estimation of ectasia in patients. Apart from differences in the transcription and inflammation processes, the CE of patients with post-LVC ectasia exhibits molecular features similar to KTCN.